2017
DOI: 10.1007/s00784-017-2083-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acidity of in-office bleaching gels on tooth sensitivity and whitening: a two-center double-blind randomized clinical trial

Abstract: Clinicians should opt to use in-office bleaching with a neutral gel than an acid product because the former causes a significant lower risk and intensity of tooth sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0
23

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 27 publications
8
77
0
23
Order By: Relevance
“…The first objective of this study was to assess the possible impact of pH on the color change comparing two in‐office bleaching gels with different pH values. The results showed that no significant difference in the color change was observed when both groups were evaluated at each time, as well as previously observed for immediate evaluation . This observation leads us to accept the first null hypothesis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The first objective of this study was to assess the possible impact of pH on the color change comparing two in‐office bleaching gels with different pH values. The results showed that no significant difference in the color change was observed when both groups were evaluated at each time, as well as previously observed for immediate evaluation . This observation leads us to accept the first null hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…This study is the 12‐month follow‐up of an earlier study registered at http://rebec.gov.br under the identification number RBR‐3h6n6c. All 12‐month recall measurements were performed in the clinic of Dental School of the local University from June 2016 to June 2017.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The acidic pH levels could reduce the mineral content of enamel and dentin. This change in the surface morphology reduces hardness properties and increases roughness . It has been reported that high concentrations of peroxide molecules can easily produce soft‐tissue burns and induce morphological changes in the enamel.…”
Section: Associated Issues To Whiteningmentioning
confidence: 99%